2007
DOI: 10.1111/j.1365-2788.2006.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and psychological well‐being in GH‐treated, adult PWS patients: a longitudinal study

Abstract: Our findings suggest that the amelioration of QoL and psychological status is sustained in patients who continue GH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 37 publications
(26 reference statements)
3
42
0
1
Order By: Relevance
“…Two studies showed that GH treatment can improve the physical and psychological aspects of health-related quality of life (HRQOL) in adolescents and adults with PWS [7,8], but information about HRQOL or the effect of GH treatment on HRQOL in children with PWS is scarce. One study investigated HRQOL in 19 adolescents after 10 years of GH treatment and observed a lower HRQOL than in the general population on the items of mobility, breathing, speech, mental function, going to school, and getting and having friends [9].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies showed that GH treatment can improve the physical and psychological aspects of health-related quality of life (HRQOL) in adolescents and adults with PWS [7,8], but information about HRQOL or the effect of GH treatment on HRQOL in children with PWS is scarce. One study investigated HRQOL in 19 adolescents after 10 years of GH treatment and observed a lower HRQOL than in the general population on the items of mobility, breathing, speech, mental function, going to school, and getting and having friends [9].…”
Section: Introductionmentioning
confidence: 99%
“…We identified nine papers that looked at QoL in other growth-related conditions treated with growth hormone. [36][37][38][39][40][41][42][43][44] Again these presented a variety of results, but only limited evidence that there is a strong link between QoL and final height gain. Several of the studies called for further research into the links between QoL and short stature and the tool with which this is evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Bertella et al 23) evaluated quality of life by physical and psychological well-being questionnaires (SF 36) self-administered by the patients or their caregivers. They found significant improvements in both scales, with greater improvements noted in patient questionnaires than in questionnaires completed by their caregivers.…”
Section: ) Quality Of Lifementioning
confidence: 99%